Challenges of human resource management in Japan - Bebenroth, Ralf; Kanai, Toshihiro, 1954- (Routledge contemporary Japan series ;, 2010)
Human resource management systems differ across corporations around the world. Japan has unique characteristics that create specific challenges for HRM and there is currently a lack of research focusing on Japanese HR issues available to westerners. This book examines the major challenges and dilemmas in human resource management as Japan's industrial society continues its resurgence in the global arena. The first part of the book deals with Japanese HRM from an international perspective, analysing the overall structure of Japanese HRM systems and comparing these with current international.